2022
DOI: 10.1186/s12864-022-08371-5
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note to: Coffee component hydroxyl hydroquinone (HHQ) as a putative ligand for PPAR gamma and implications in breast cancer

Abstract: This article has been retracted. Please see the Retraction Notice for more detail:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Additionally, caffeine not only affects immune cells, such as T and B lymphocytes, NK cells and macrophages, but also affects cytokines, such as TNF-α and IL-2, which have a variety of functions, to improve immunity in the body (68) . Moreover, caffeine may represent a therapeutic agent for BC by activating apoptosis-inducing mechanisms (69) . Therefore, the intake of decaffeinated coffee is not as effective as total coffee consumption, and similar results have been reported in published studies (70)(71) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, caffeine not only affects immune cells, such as T and B lymphocytes, NK cells and macrophages, but also affects cytokines, such as TNF-α and IL-2, which have a variety of functions, to improve immunity in the body (68) . Moreover, caffeine may represent a therapeutic agent for BC by activating apoptosis-inducing mechanisms (69) . Therefore, the intake of decaffeinated coffee is not as effective as total coffee consumption, and similar results have been reported in published studies (70)(71) .…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyl hydroquinone (HHQ) is another coffee compound potentially useful for breast cancer treatment. HHQ isolated from coffee inhibited growth of MDA-MB-231 and MCF-7 cells with half maximal inhibitory concentration (IC 50 ) value of 25 μM/ml and 50 μM/ml, respectively [80]. The study showed that HHQ induced ROS generation as well as compromised the permeability of mitochondria membrane.…”
Section: Breast Cancermentioning
confidence: 94%
“…The activity, efficacy and safety of deoxyarbutin dA is safer and less cytotoxic compared with hydroquinone [96]. Based on in vitro experiments against mushroom tyrosinase, it turns out that dA effectively inhibits mushroom tyrosinase with Ki 10 times lower than hydroquinone and 350 times lower than arbutin.…”
Section: Fig 2: Conversion Of Arbutin Compound Into Damentioning
confidence: 99%